Investigating the Stereochemistry of α-Carbon in Lignin Preparations and Lignin Model Compounds Using 77Se NMR - Mahnaz Oghbaie; Seyed Ahmad Mirshokraie; Abdol H. Massoudi (BioResources, 2015)
Studying the stereochemistry of lignin as a natural chiral polymer may have scientific and technical importance regarding the behavior of lignin and delignification processes. In the present study, the hydroxyl groups of α-carbon (chiral center) in phenyl propane structural units of lignins and two model compounds were selenated. Then, the 77Se nuclear magnetic resonance (NMR) spectra of the selenated samples were examined in order to determine the ratio of diastereomers (erythro and threo). The results revealed that lignins are a mixture of different ratios of two diastereomers. This finding may have scientific importance and practical impacts on the chemistry of delignification processes and other related phenomena in the domain of pulp and paper sciences.